Labor Law and Social Insurance Law: A Case Study of the Hashemite Kingdom of Jordan - Jaber Abdullah Al-Zubaidi; Hussein Jasser Saqr (International Journal of Law Research and Studies, 2024)
In light of the major transformations and developments witnessed in various business fields, and with the increase in the size of organizations, the number of employees, the founding capital, and the rate of investment in various countries, it has become necessary to have a legal system that regulates the work within these organizations. This system aims to prevent disputes and protect the rights of the parties concerned, whether they are employers or workers, both constitute the basis for the continuation of the productive process; The employer bears responsibility for the operation and continuity of work, while the workforce represents the main driver of this activity. Labor law, in its general sense, is a set of legislation and procedures that aim to achieve understanding between those responsible for employment in institutions and their workers. The law ensures that each party is informed of his rights and duties, which protects the rights of all parties. As one of the main branches of the law, it forms an essential part of the laws regulating business in every country. Countries around the world, and in the event of disagreements between business parties, cases are submitted to the judiciary for adjudication. This research presents the definition of work, the worker, types of employment contracts, conditions for terminating employment contracts, types of vacations, laws regulating strikes, Jordanian labor law, and social insurance law.